2016
DOI: 10.1002/prot.25159
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility and dynamics of protein disulfide isomerase

Abstract: We have studied the mobility of the multidomain folding catalyst, protein disulfide isomerase (PDI), by a coarse‐graining approach based on flexibility. We analyze our simulations of yeast PDI (yPDI) using measures of backbone movement, relative positions and orientations of domains, and distances between functional sites. We find that there is interdomain flexibility at every interdomain junction but these show very different characteristics. The extent of interdomain flexibility is such that yPDI's two activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 52 publications
4
43
0
Order By: Relevance
“…We focus on the lowest frequency nontrivial modes of motion, which represent large‐scale motions that are likely to be on relatively long (ms) timescales. Recent studies have shown excellent agreement between flexible motion simulations and large‐scale functional motion in enzymes, with results from the calculations found to be consistent with those produced by molecular dynamic simulations . Example results are shown in Fig.…”
Section: Resultsmentioning
confidence: 65%
“…We focus on the lowest frequency nontrivial modes of motion, which represent large‐scale motions that are likely to be on relatively long (ms) timescales. Recent studies have shown excellent agreement between flexible motion simulations and large‐scale functional motion in enzymes, with results from the calculations found to be consistent with those produced by molecular dynamic simulations . Example results are shown in Fig.…”
Section: Resultsmentioning
confidence: 65%
“…We have applied this method to explore the flexibility of yPDI [74] and hPDI [75] , and summarise the results here; full descriptions of the simulated trajectories, expressed as a series of PDB data files, plus other analyses can be found on the associated web-site [75] . The analyses were based on the original high resolution yPDI structure 2B5E [12] , and the oxidized ( 4EL1 ) and reduced ( 4EKZ ) hPDI structures [14] .…”
Section: Modelling the Flexibility Of Pdimentioning
confidence: 99%
“…PDI is a highly flexible molecule that exhibits a particularly high degree of flexibility in the b'-x-a' region. In its reduced form, PDI can assume a very compact structure, enabling interaction of the N-terminal and C-terminal active site motifs [13,14]. In contrast, oxidized PDI demonstrates a more extended confirmation, as evidenced by high resolution evaluation of crystal structure [15] and small angle x-ray scattering [16].…”
Section: Pdi Structure-functionmentioning
confidence: 99%